Predictors of Poor Glycemic Control among Patients with Type 2 Diabetes in Southern Afghanistan: A Multicenter Cross-sectional Study - Fazli, Najibullah; Stanikzai, Muhammad Haroon; Kumar; S V Vinod; Dadras, Omid (Medknow Publications, 2026)
Poor glycemic control is associated with an increased risk of diabetes-related complications, attributable to a wide range of factors. The aim of this study was to determine the prevalence and predictors of poor glycemic control among patients with type 2 diabetes in southern Afghanistan. We conducted a cross-sectional study among diabetes patients randomly recruited from four hospitals in southern Afghanistan during their follow-up visits between August and October 2024. Out of 406 patients, 74.9% (95% confidence interval [CI]: 70.3%-79.1%) had poor glycemic control. Physical inactivity (adjusted odds ratio [AOR] =1.89, 95% CI: 1.04-3.41), irregular monitoring of blood glucose levels (AOR = 8.80, 95% CI: 4.49-17.2), nonadherence to antidiabetic medications (AOR = 2.69, 95% CI: 1.41-5.13), and presence of depression symptoms (AOR = 2.20, 95% CI: 1.25-3.86) were significant predictors of poor glycemic control. The findings highlight an urgent need for targeted health policies and clinical interventions to address the high prevalence of poor glycemic control in Afghanistan.